State and trends of regulation of crypto assets and cryptocurrency exchanges - M. B. Kitinov (Вестник университета, 2025)
This article analyses the current state and trends in the regulation of trading of crypto assets and crypto exchanges at the global level. The enacted laws and regulations of the jurisdictions of the United States of America (herein-after referred to as USA) and the European Union (hereinafter referred to as EU) are indicated. It is emphasised that the regulatory framework of the EU is an example of effective international regulation. It is noted that the legislation in the USA regarding the regulation of the crypto exchanges and crypto assets is at the development stage, and there are contradictions between authorities considering the scope of the necessary regulation. The steps that should be taken at the global level to harmonise regulatory standards are analysed. The key directions for the development of the global regulation of the crypto exchanges include expansion of requirements to combat money laundering and financing of terrorism, introduction of mechanisms for training and protecting investors and information disclosure requirements. The author emphasises the need for interaction between industry representatives and regulators to manage the risks associated with cryptocurrencies, including prevention of market manipulation and fraud. The results of the work will be useful in shaping the concepts of the national and global regular framework regarding the trading of the crypto assets. Methods of analysis, synthesis, formal-logical, comparative, and descriptive analysis have been used as research methods.